Assessment of the Safety of Enoxaparin a Low Molecular Weight Heparin for Prophylaxis against Deep Venous Thrombosis in Patients with Chronic Kidney Disease on Hemodialysis - Vadi, Sonali; Shah, Sanjay P.; Yim, Kenneth; Egbunike, Ifeanyi (Archives of Clinical and Biomedical Research, 2022)
Study objective To analyze the incidence of complications following enoxaparin use in patients on hemodialysis. Study design and patients This retrospective chart review study included 200 patients equally divided into two groups, those who received enoxaparin and those who were administered unfractionated heparin (UFH). Primary hypothesis was that enoxaparin is safe and equally effective as UFH for the prophylaxis of venous thromboembolism (VTE) in chronic kidney patients on hemodialysis in adjusted dosage. Safety parameter assessed was the incidence of bleeding. Secondary end point was that enoxaparin is safe as UFH in the elderly patients on hemodialysis in adjusted dosage. Measurements and main results There were no significant differences in any of these parameters except that patients in the Enoxaparin group had a greater decline in platelets compared to the UFH group. Overall incidence of bleeding requiring packed red cell transfusion was 3 in LMWH group vs. 2 in UFH group, p = NS. None of the patients developed DVT during the therapy. There was no statistical difference between the groups in primary outcomes for patients > 65 years of age. Conclusion The incidence of venous thromboembolism and bleeding complications were low suggesting that further evaluation of enoxaparin in this specific population is warranted.